Clinical observation and electroretinogram analysis of ocular siderosis following ocular trauma: a retrospective case series - Qu, Yuyao; He, Liwen; Ma, Jixian; Hu, Yaguang; Li, Jingming; Bai, Xiaolong (Frontiers in Medicine, 2025)
BackgroundTo observe demographics and clinical characteristics of patients with ocular siderosis and to further analyze corresponding changes in electroretinogram (ERG) findings.MethodsThe demographics and clinical characteristics from patients with ocular siderosis were collected and summarized, including sex, age, disease duration, visual acuity, and intraocular pressure. ERG parameters, including a-wave and b-wave latencies in photopic ERG and both amplitude and latency of b-wave in scotopic ERG, were collected. Paired comparisons were conducted to verify the difference between the affected eye and unaffected eye within the same individual.ResultsA total of 15 patients with unilateral ocular siderosis were included, of whom 13 were male. The average age was 38.6 years. More than half of the affected eyes exhibited severely impaired visual acuity (≤0.02). Significant differences were observed between affected and unaffected eyes in the b-wave amplitude and latency in photopic ERG, b-wave amplitude in scotopic 0.01 ERG, and both a-wave and b-wave amplitudes and latencies in scotopic 3.0 ERG.ConclusionOcular siderosis is associated with marked retinal dysfunction, particularly involving the inner retinal layers. ERG proves to be a valuable tool for detecting and evaluating early retinal impairment in ocular siderosis, offering clinicians critical insights for timely diagnosis, management, and disease monitoring.